1997
DOI: 10.1164/ajrccm.155.1.9001282
|View full text |Cite
|
Sign up to set email alerts
|

Increasing incidence of withholding and withdrawal of life support from the critically ill.

Abstract: To determine whether limits to life-sustaining care are becoming more common, we attempted to quantify the incidence of recommendations to withhold or withdraw life support from critically ill patients, to describe how patients respond to these recommendations, and to examine how conflicts over these recommendations are resolved. In 1992 and 1993 we prospectively enrolled 179 consecutive patients from two intensive care units (ICUs) for whom a recommendation was made to withhold or withdraw life support. Where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
289
3
8

Year Published

1998
1998
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 668 publications
(318 citation statements)
references
References 26 publications
18
289
3
8
Order By: Relevance
“…The views of year 5 medical students were in line with those of practicing clinicians documented in previous studies. 19,[21][22][23][24][25][26][27][28] These changes with the years of medical education suggest that the differences between medical and non-medical students are due to the medical school experience and not selection of people with intrinsically different views. The absence of an age-related effect in non-medical students suggests that these changes are not an age-related phenomenon but are related to the medical school experience.…”
Section: Discussionmentioning
confidence: 99%
“…The views of year 5 medical students were in line with those of practicing clinicians documented in previous studies. 19,[21][22][23][24][25][26][27][28] These changes with the years of medical education suggest that the differences between medical and non-medical students are due to the medical school experience and not selection of people with intrinsically different views. The absence of an age-related effect in non-medical students suggests that these changes are not an age-related phenomenon but are related to the medical school experience.…”
Section: Discussionmentioning
confidence: 99%
“…1 Several studies have been published, especially in the USA, since 1990, that question the principle of life at any cost. 2,3 End-of-life decisions are now widely discussed, placing a high value on the respect for the patient, including a growing concern with maintaining dignity at the end of life and humanization of death. 4 Concomitantly, the concept of life support limitation (LSL), which includes do-notresuscitate orders, and withholding and withdrawal of life support, has appeared in medical practice to avoid the use of treatments that only prolong life but do not improve patient outcome, usually leading to useless treatments and needless suffering.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last two decades, studies have identified substantial biases in the end-of-life decision-making process [9][10][11][12][13]. These biases may account for considerable practice differences that cannot be explained by routinely collected information.…”
Section: Introductionmentioning
confidence: 99%
“…Last, discrepancies have been reported across countries in the incidence of death after DFLSTs, characteristics of patients who die after DFLSTs, and weight given to the patient's and family's opinion [4,7,8]. In addition to cultural specificities, legislation may substantially affect practices regarding end-of-life decisions [2,12,16,[21][22][23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation